Literary Cultures and Public Opinion in the Low Countries, 1450-1650 - Bloemendal, Jan (Brill's Studies in Intellectual History, 2011)
In the early modern Low Countries, literary culture functioned on several levels simultaneously: it provided learning, pleasure, and entertainment while also shaping public debate. From a ditty in Dutch sung in the streets to a funeral poem in Latin composed to be read for or by intimate friends, from a play performed for a prince to a comedy written for pupils - literary texts and performances often dealt with highly controversial topics of religion or politics, on a local or national, but also on a supranational scale. This volume sets out to analyse the role and function of literary culture in the formation of early modern public opinion, and proposes ways in which a modern scholar might approach early modern works of literature and other traces of literary culture to explore early modern public opinion making. The cases presented in this volume bring the Dutch and Latin literary cultures of the Low Countries in the focus of international debates on the history of public opinion.